Soil-landforms interdependencies and weathering at Admiralty Bay, King George Island, Maritime Antarctica - Zieliński, Artur; Krupa-Kurzynowska, Joanna; Rachlewicz, Grzegorz; Jarzyna, Krzysztof (Quaestiones Geographicae, 2025)
Soil formation in polar regions is relatively weakly recognised due to their rarity and spatial dispersion. The main pedological, sedimentological and cryogenic features of the ice-free coasts of Admiralty Bay were described and quantified with an emphasis on the relationship between frost weathering and soil distribution in different landforms. Soil sites were classified according to their location in the profile from the glacier margin in the late 80s of the 20th century to the coast of the bay and investigated in terms of sediment grain characteristics. The studied soil-forming sediments are typical for glacial and periglacial processes in neutral and acidic environments. Soil composition exhibits considerable textural differentiation and depends on the geology and landforms of the association, but first, on contemporary glacial and periglacial processes. Weathered debris and sediments in the ice-free area contain abundant skeletal elements, especially in morainic sediments. Mineral grains in glacier ice are subjected to intensive cryogenic processes, micro-exfoliation and granular micro-disintegration, forming fine-grained fractions. Coastal deposits on raised marine terraces exhibit polygenic features due to their enrichment by fluvial, niveofluvial, glaciofluvial, slope and aeolian sedimentation. Extensive and superficial exfoliation of particles predominates and is typical for frost weathering. The morphology of grain surfaces indicates a slightly aggressive influence on seawater. Therefore, weathered layers are not removed and no etching of quartz grain surfaces is noted. Different variants of Cryosols with Andic, Skeletic, Coarsic, Fluvic, Ornithic, Humic or Gleyic qualifiers were identified in the study area, as well as Turbic Leptosols on one site.